The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/pon.5877
|View full text |Cite
|
Sign up to set email alerts
|

Return to work after cancer: Improved mental health in working cancer survivors

Abstract: Objective Aim of the study was to compare working and non‐working patients over a period of 12 months regarding socio‐demographic, cancer‐specific and mental health parameters. Methods This study was conducted as part of a Germany‐wide longitudinal survey among 1398 patients in 13 national Comprehensive Cancer Centers. The sample used for analysis consisted of n = 430 cancer patients younger than 65 years (age M = 52.4 years, SD = 8.1; 67.0% females). Socio‐demographic, cancer‐specific and mental health parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…36 Lieb et al reported that non-workers had higher levels of depression, anxiety, and distress than workers. 9 Yang et al study on the return to work and…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Lieb et al reported that non-workers had higher levels of depression, anxiety, and distress than workers. 9 Yang et al study on the return to work and…”
Section: Discussionmentioning
confidence: 99%
“…8 It has been reported that returning to the workplace by patients with cancer who had previously worked improves their mental health and prognosis. 9,10 For employees with cancer to balance work and treatment, support from employers and coworkers and their understanding of cancer and its treatments are important.…”
mentioning
confidence: 99%
“…A PHQ-9 total score ≥5 indicated MDD, while a GAD-7 total score ≥5 indicated anxiety. The severity of MDD was graded as Grade I (5-9), Grade II (10)(11)(12)(13)(14), Grade III (15)(16)(17)(18)(19), and Grade IV (20)(21)(22)(23)(24)(25)(26)(27). Anxiety severity was graded as Grade I (5-9), Grade II (10)(11)(12)(13)(14), and Grade III (15)(16)(17)(18)(19)(20)(21).…”
Section: Questionnaire Of Mental Assessments and Quality Of Lifementioning
confidence: 99%
“…Stress factors have multiplied, especially among working women, making them more psychologically vulnerable than they were before this pandemic and easy prey to psychological distress. Also, the sweeping physiological effects of COVID-19 infections in 2020 and 2021, the psychosocial impacts of lockdowns, social distancing, and the associated disruptions to daily life have brought on a simultaneous mental health crisis, particularly among many working mothers who are disproportionately balancing childcare, virtual schooling, and employment vulnerability [13,14]. However, there are also studies underpinning our results that did not find any association of socio-demographic data with return to work, such as sex, [15,16] age, [17] marital status [18] and education.…”
Section: Literature Reviewmentioning
confidence: 99%